Is musical ability related to second-language acquisition? A meta-analysis - Rachel M. Thompson; Lauren K. Salig; L. Robert Slevc (Royal Society Open Science)
In our multicultural and interconnected world, the ability to learn new languages is important. However, there are significant differences in how successfully adults can learn aspects of non-native languages. Given robust relationships between musical ability and native-language processing, musical ability might also contribute to successful second-language acquisition. However, while several studies have assessed this relationship in various ways, the consistency and robustness of the relationship between musical ability and second-language learning remains unclear. Thus, we synthesized 184 effects across 57 independent studies (n =3181) with a robust variance estimation multivariate meta-analysis, and we narratively summarized partial correlation effects across 12 studies. The available evidence suggests that musical ability is indeed positively related to second-language learning, even after factoring in publication bias revealed by the meta-analysis. Although future work with more diverse participant populations and methodologies is needed to further disentangle this relationship, it is apparent that individuals with better musical ability are generally more successful at second-language learning.